Peningkatan Efisiensi Verifikasi Identitas Pegawai Melalui Digitalisasi ID Card Terintegrasi QR Code Studi Kasus BKPSDMD Kota Jambi - Andreo Yudertha; Aldi Darmawan; Rega Ardiansah; Amelia Aisaturadia; Diva Angeliana (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The process of creating and verifying employee ID cards at BKPSDMD Jambi City was previously carried out manually, resulting in lengthy processing times, data entry errors, and a high risk of identity forgery. This study aims to design and implement a web-based employee ID card digitalization system integrated with QR Code technology to improve the efficiency, accuracy, and security of employee identity verification. The system was developed using the Waterfall methodology, consisting of requirements analysis, system design, implementation, testing, and maintenance. The application was built using Native PHP, MySQL, HTML, CSS, and JavaScript. Functional testing was conducted using Black Box Testing with 12 test scenarios, while usability evaluation employed the System Usability Scale (SUS) involving 20 respondents. The results indicate that all core system features functioned properly, achieving a 100% success rate on valid test scenarios. Furthermore, the usability evaluation produced an average SUS score of 71.75, which falls into the good and acceptable categories. The implementation successfully accelerated the ID card issuance process, improved data management accuracy, and enhanced identity verification security through QR Code integration directly connected to the employee database. Therefore, the developed system effectively supports digital transformation and improves the efficiency of employee identity management at BKPSDMD Jambi City.